Modgangen kom ind i verden ved Adam (og Eva): At læse 1 Mos 2-3 uden Rom 5 - Liebermann, Rosanne (Dansk Teologisk Tidsskrift, 2025)
Paul’s interpretation of Genesis 2-3 as a story about Adam’s “fall” and the universal origins of sin and death (Romans 5:12) has had an immense impact on Christian theology. Even though biblical researchers have long recognized that this interpretation is by no means self-evident in the Old Testament text, some have continued even in recent years to read Genesis 2-3 through the lens of Romans 5. In this article, I examine both the interpretational traditions that led Paul to his reading of Genesis 2-3 and those that tend to inspire contemporary academic interpretations of the same text. I conclude with my own reading of the Garden of Eden story as an etiology for why human lives in ancient Syria-Palestine tended to be short and full of hardship, discussing how the narrative functions as a fitting introduction to the Pentateuch. The purpose is not to argue for one “correct” understanding of Genesis 2-3, but to demonstrate how different motivations underlie different interpretations—and that it is important to be explicit about what those motivations are.